2016
DOI: 10.1002/joc.4635
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation of temperature, precipitation and wind trends in a desertification prone region of China from 1960 to 2013

Abstract: Spatial and temporal distributions of temperature, precipitation and wind speed from 1960 to 2013 at 179 meteorological stations situated in the desertification prone region (DPR) of China are analysed using the Mann-Kendall test and the Theil-Sen's slope estimator on monthly, seasonal and annual timescales. The results indicate that annual mean temperature has increased at a rate of 0.33 ∘ C (10 year) −1 over the DPR. T min generally increased at a higher rate than T max in the majority of the months and seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…A great many statistical methods have been developed to detect the trend in long-time series of hydro-meteorological variables, including parametric and non-parametric methods [43][44][45]. The non-parametric Mann-Kendall (MK) test [46,47] is a valid tool for assessing the significance of monotonic trends in hydro-meteorological time series; it is suitable for non-normally distributed data, including missing values, and it is less influenced by the presence of outliers in the data [48]).…”
Section: Statistic Analysismentioning
confidence: 99%
“…A great many statistical methods have been developed to detect the trend in long-time series of hydro-meteorological variables, including parametric and non-parametric methods [43][44][45]. The non-parametric Mann-Kendall (MK) test [46,47] is a valid tool for assessing the significance of monotonic trends in hydro-meteorological time series; it is suitable for non-normally distributed data, including missing values, and it is less influenced by the presence of outliers in the data [48]).…”
Section: Statistic Analysismentioning
confidence: 99%
“…Trends for individual station data and regional series were estimated and the significance of the trends was determined using the Mann-Kendall test [40,41], which does not assume that data are normally distributed, and robustly responds to the effects of outliers in the series and has been widely used to test trends in hydrological and meteorological data [29,[42][43][44][45], and the 10% level of statistical significance was used. Sen's slope estimator was used to estimate the true slope of an existing trend (the change per year) [46].…”
Section: Interpolation and Trend Analysis Of Indicesmentioning
confidence: 99%
“…The results for the climatic trends for T a , T max , T min and DTR were 0.204, 0.248, 0.233 and 0.003 °C (10 years) −1 , respectively, these being lower than the corresponding results for the whole of the Loess Plateau (Shi et al , ) and for the desertification‐prone area of China (Shi et al , ). Although climate warming was predominantly linked to increased emissions of anthropogenic greenhouse gases and aerosols (IPCC, ; Najafi et al , ; Xu et al , ), agricultural irrigation‐induced cooling effects may partly compensate for greenhouse gas warming (Bonfils and Lobell, ; Cook et al , ), effects which have been observed or simulated by previous investigations (Lobell et al , ; Sacks et al , ; Han and Yang, ; Huber et al , ).…”
Section: Discussionmentioning
confidence: 99%